Tinjauan Kriminologi Terhadap Tindak Pidana Judi Online Studi Kasus Omzet Jaringan Judi Online Capai Rp 2,2 Milyar di Batam - Mulya, Agres Setia (UM Purwokerto Press, 2024)
This study aims to analyze and find out about the factors that cause online gambling and find out how the action will be taken by the government and law enforcement agencies against online gambling activities that occur in the city of Batam. Regulation of online gambling crime in Indonesia is regulated in Law No. 19 of 2016 on amendments to Law No. 11 of 2008 on information and Electronic Transactions (UU ITE), containing provisions regarding gambling conducted online via the internet in Article 27 paragraph (2) which reads “Any person intentionally without the right to distribute, transmit and/or make accessible information or documents that have a prohibition of gambling-charged acts. The punishment for this violation is regulated in Article 45 paragraph (2), namely “any person intentionally and without the right to distribute and/or transmit and/or make accessible electronic information and/or electronic documents that have a gambling charge as intended in Article 27 paragraph (2) of the ITE Law shall be sentenced to a maximum of 6 (six) years in prison or a maximum fine of Rp. 1 billion”.